Dependence of the properties of the Fe-Cr-Ni alloy on the composition and properties - Hlushkova, D.; Глушкова, Д. Б. (Харківський національний автомобільно-дорожній університет, 2024)
This study employed a multifractal approach to assess the heterogeneous structure of the Fe-Cr-Ni alloy. Goal. The calculation of the spectrum of dimensionalities for microstructural elements (pearlitic matrix, carbides, and graphite) was conducted using the Rényi formula. Methodology. New relationships were established between the structure and properties of the alloy (such as hardness and impact strength), which are described by models allowing prediction of properties from microstructure images. Results. Most of the derived correlations exhibit a linear nature, indicating that not only does the percentage content of a particular structural element influence its properties, but also the shape of the element, as characterized by its fractal dimension, contributes to those properties. Analytical method that can be useful for assessing and improving the characteristics of alloys. Practical value. The essence of the work has a practical value particularly when precise determination of properties is critically important for their application in various fields of science and engineering.
Залежність властивостей сплаву Fe-Cr-Ni від складу та властивостей
Keywords: Fe-Cr-Ni alloy; properties; composition; structure; multifractal; model; 620.175.2:669.15; 10.30977/BUL.2219-5548.2024.105.0.27